Kualitas Sosis Ikan Nila dengan Penambahan Puree Kulit Buah Naga Merah - Syahkira, Syahkira; Faridah, Anni (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aimed to evaluate the effect of adding red dragon fruit peel (Hylocereus polyrhizus) puree on the sensory quality of Nile tilapia (Oreochromis niloticus) sausage, covering color, fishy odor, dragon fruit peel aroma, texture, umami taste, and dragon fruit peel flavor. A completely randomized design with four treatments, X0 (0%, control), X1 (20%), X2 (40%), and X3 (60%), was applied, each replicated three times. Sensory evaluation was performed by 30 untrained panelists using a hedonic scale, and data were analyzed using ANOVA followed by Duncan’s multiple range test. The results indicated that the addition of red dragon fruit peel puree significantly improved color quality, with X3 achieving the highest score. Fishy odor tended to decrease with increasing puree concentration, while the aroma and flavor of dragon fruit peel increased, although these changes were not statistically significant. Texture and umami taste showed a slight decrease at higher concentrations but remained within acceptable sensory limits. Overall, X3 provided the most attractive visual quality without compromising sensory acceptability. These findings suggest that incorporating red dragon fruit peel puree can enhance the market appeal of Nile tilapia sausage while adding value to agro-industrial waste as a natural colorant and antioxidant source.